Bottom-up macro exposures and relation to expected returns - Sinivuori, Joel (My University, 2026)
This thesis will review the relationship between macroeconomic risk and expected returns based on the previous asset pricing literature. Classical research has been based largely on aggregated macroeconomic variables and so-called top-down approaches, which cannot always identify differences between companies on the macroeconomic exposures. In the central part of the thesis are bottom-up exposures, where macroeconomic risk is examined through firm-level qualities, factor-based portfolios, and return-based measures. The reviewed literature suggests that firms that are more sensitive to unfavorable macroeconomic circumstances gain higher expected returns on average as compensation for bearing systematic risk. In addition, macroeconomic exposures fluctuate significantly between industries and firms, and their significance is highlighted especially in economic uncertainties. According to the literature, bottom-up approaches complement traditional asset pricing models by offering a more precise and flexible way to review how macroeconomic risk is shown in expected returns on a firm-level.
Keywords: macroeconomics; security market; risks; yield; investments (economics); econometrics; Bachelors of Science (Economics and Business Administration); investments; finance; investors; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; fi=Kauppatieteiden kandidaattiohjelma|en=Bachelor Programme in Business Studies|